Penggunaan Retrospective Think Aloud Dan System Usability Scale Pada Edlink Mobile pada Universitas Primakara - Gunawan, Putu Amelia Chrysilla; Utami, Nengah Widya; Dewi, Eka Grana Aristyana (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2024)
One of the IT campuses in Denpasar - Bali, Primakara University has used e-learning to help activities for the campus community, especially students. Primakara initially used Moodle-based e-learning called SPADA, then used Edlink when its status changed to a university. To find out students' difficulties when using Edlink mobile, it is necessary to carry out a usability evaluation. Usability can identify problems with the system design that can be experienced by users so that they can be corrected and minimize user errors. The use of the RTA technique is to determine the obstacles or problems experienced by users, while the SUS technique is to determine the level of user satisfaction. From the RTA technique, it can be seen that most of the problems faced by users are difficulty finding features because their location is hidden or the name does not match the purpose of the feature. The level of user satisfaction also shows poor results because the user's SUS score is 56.24. This score is included in grade D with an OK category, a marginal level of user acceptance, and a detractor net promote score. It can be concluded that the results of the usability evaluation of Edlink mobile at Primakara University are not good so improvements or reassessment are recommended to improve the quality of Edlink mobile.